Effect of Sales Growth, Profitability, Firm Size and Leverage on Tax Avoidance: (Case Study of Automotive Companies on the Indonesia Stock Exchange 2017 – 2021) - Nur Adinda Kholifah; Ariyani (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the Effect of Sales Growth, Profitability, Company Size and Leverage on Tax Avoidance in Automotive Companies on the Indonesia Stock Exchange in 2017 – 2021. This study uses a quantitative approach. The sampling technique used in this study used a purposive sampling approach, the number of samples used in this study were 38 samples. The results of this study indicate that sales growth has an effect on tax avoidance, profitability has no effect on tax avoidance, company size has an effect on tax avoidance, company size has an effect on tax avoidance and sales growth, profitability, company size and leverage have an effect simultaneously on tax avoidance. This research limits the problem that is taken, which lies in the object where this research limits only using Automotive Companies on the Indonesia Stock Exchange in 2017 - 2021 then researchers also limit the variables used, namely the independent variables Sales Growth, Profitability, Company Size and Leverage and the dependent variable tax avoidance. For companies, it can be used as a useful consideration for making decisions related to better policies regarding tax avoidance that occur in companies.